2018
DOI: 10.4236/aim.2018.81004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aflatoxigenic Fungi and Detection of Their Aflatoxin in Red Chilli (<i>Capsicum annuum</i>) Samples Using Direct Cultural Method and HPLC

Abstract: Aflatoxins are the potential lethal toxin produced by Aspergillus sp. important health hazard throughout the world. In this study, 26 Aspergillus sp. have been isolated from 50 samples of red chilli collected throughout the country. These 26 isolates were grown primarily on agar media to identify the aflatoxin producing species. It is possible to distinguish A. flavus strains from other Aspergillus sp. developing orange colour on the reverse of the plates. The Coconut Cream Agar (CCA) is used to detect aflatox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The AFPA is a selective media that identifies various Aspergillus species and gives the distinct characteristic color of many Aspergillus species especially A. flavus, A. parasiticus and A. niger. Many researchers have previously identified Aspergillus flavus using AFPA (Abriba et al, 2013;Fakruddin et al, 2015;Hossain et al, 2018). In the current study, one of the isolates was shown to be A. niger because it produced pale yellow to white hyphae, turning to dark brown to black on AFPA, which is in agreement to the previous results (Abriba et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The AFPA is a selective media that identifies various Aspergillus species and gives the distinct characteristic color of many Aspergillus species especially A. flavus, A. parasiticus and A. niger. Many researchers have previously identified Aspergillus flavus using AFPA (Abriba et al, 2013;Fakruddin et al, 2015;Hossain et al, 2018). In the current study, one of the isolates was shown to be A. niger because it produced pale yellow to white hyphae, turning to dark brown to black on AFPA, which is in agreement to the previous results (Abriba et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…On the reverse side of the AFPA culture plate, it also showed characteristics bright orange color. Though, AFPA was previously used for the identification of Aspergillus flavus (Hossain et al, 2018) yet the toxigenic potential is not usually determined by this media. While, to determine the toxigenic potential of A. flavus, APA media is used which shows a zone of toxin formation (in case of toxigenic fungus) under UV light (365nm).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations